The effects of compensatory acceleration on upper-body strength and power in collegiate football players - Jones, G.; Hunter, G.; Fleisig, G.; Escamilla, R.; Lemak, L. (The Journal of Strength and Conditioning Research, 1999)
The purpose of this study was to compare the effects of maximum concentric acceleration training versus traditional upper-body training on the development of strength and power of collegiate NCAA Division 1AA football players. Power was tested with a seated medicine ball throw (n = 30) and a force platform plyometric push-up test (n = 24). Upper-body strength was tested by using a bench press with 1 repetition maximum (1RM) (n = 30). All players were on an identical off-season weight-training program. The control group performed exercises with conventional concentric velocity, and the experimental group performed the concentric phase of each repetition as rapidly as possible. Two-way repeated-measures analysis of variance was used to determine training and group ifferences. Significant training effects for all strength and power measures indicated that both groups increased strength and power. Significant training by group interaction indicates the experimental group increased significantly more than the control group in the bench press (+9.85 kg vs. +5.00 kg) and throw (+0.69 m vs. +0.22 m). Significance was not reached for any of the training by group interactions for force platform variables (amortization time 0.46 seconds for the experimental group vs. 0.22 seconds for the control group; average power was +365 W for the experimental group vs. +108 W for the control group). The results of this study support the use of maximal acceleration of concentric contractions by collegiate football players during upper-body strength and power training.